2022
DOI: 10.1155/2022/3099409
|View full text |Cite
|
Sign up to set email alerts
|

Cycloastragenol Confers Cerebral Protection after Subarachnoid Hemorrhage by Suppressing Oxidative Insults and Neuroinflammation via the SIRT1 Signaling Pathway

Abstract: Subarachnoid hemorrhage (SAH) is an acute cerebral vascular disease featured by oxidative insults and neuroinflammation. Cycloastragenol (CAG), the major active component of Astragalus radix, has a wide range of biological functions. However, the potential beneficial effects and the underlying molecular mechanisms of CAG on SAH remain obscure. In the current study, the cerebroprotective effects and mechanism of CAG on SAH were evaluated both in vivo and in vitro. Our results indicated that CAG significantly su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The increased expression of SIRT1 has been reported to have a neuroprotective effect on brain edema and endogenous protection against DCI after SAH, as well as inducing the attenuation of neurovascular dysfunction following SAH ( 226 228 ), and the p53 pathway regulated by endogenous SIRT1 can crucially affect BBB permeability and brain edema after SAH ( 226 ). Concomitant with FOXO1, NF-кB, and p53 decreased acetylation, activation of SIRT1 pathways after SAH markedly reduced the levels of IL-1β, IL-6, and TNF-α; decreased Bax and cleaved caspase-3 levels and microglial activation; and increased Bcl-2 expression ( 229 , 230 ). In EBI after SAH, pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) and neural apoptosis were also suppressed by resveratrol (RSV) via the AMPK/SIRT1 cascade ( 157 ).…”
Section: Immune Inflammation Relevant Signaling Pathways In Sahmentioning
confidence: 99%
“…The increased expression of SIRT1 has been reported to have a neuroprotective effect on brain edema and endogenous protection against DCI after SAH, as well as inducing the attenuation of neurovascular dysfunction following SAH ( 226 228 ), and the p53 pathway regulated by endogenous SIRT1 can crucially affect BBB permeability and brain edema after SAH ( 226 ). Concomitant with FOXO1, NF-кB, and p53 decreased acetylation, activation of SIRT1 pathways after SAH markedly reduced the levels of IL-1β, IL-6, and TNF-α; decreased Bax and cleaved caspase-3 levels and microglial activation; and increased Bcl-2 expression ( 229 , 230 ). In EBI after SAH, pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) and neural apoptosis were also suppressed by resveratrol (RSV) via the AMPK/SIRT1 cascade ( 157 ).…”
Section: Immune Inflammation Relevant Signaling Pathways In Sahmentioning
confidence: 99%
“…Further experiments showed that MDA and Fe 2+ were increased in the AP-AKI group, and GSH levels were decreased, which indicated that EVs could aggravate renal ferroptosis and lipid peroxidation (Figure 2B). As shown in a previous study, TECs are damaged by AP-AKI [7]. GPX4 and COX-2 are the essential regulators and the most important ferroptosis markers [33,35].…”
Section: Circulating Blood-derived Evs Of Ap Aggravate Ferroptosis In...mentioning
confidence: 86%
“…Tubular epithelial cells (TECs) account for 90% of the kidney volume and are damaged by AP-AKI [7]. Recent studies have shown that several forms of regulated cell death (RCD), including apoptosis, necrosis (Toll-like receptor/ZBP1-RIPK3 mediated), mitochondrial permeability transition-mediated regulated necrosis (MPT-RN), pyroautophagy (PARP1-dependent), pyroptosis (caspase1-IL-18/IL-1β mediated) and ferroptosis (GPX4 mediated), all participate in AKI [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In order to further confirm that telomere erosion is the mechanism of bone loss caused by HKSA, the most recognized telomere protector, CAG [ 33 ], was used to rescue telomere damage caused by HKSA. The results showed that the telomere length of HKSA + CAG mice was significantly longer than that of HKSA mice, and the TIF signal was the opposite, suggesting that CAG improved HKSA-induced telomere damage.…”
Section: Discussionmentioning
confidence: 99%